2022
DOI: 10.21037/atm-22-200
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of 4 GLP-1RAs in the treatment of obesity in a US setting

Abstract: Background: The number of obese people continues to increase worldwide, and obesity-related complications add to every country's health burden. Consequently, new weight-loss medications, such as glucagon-like peptide-1 receptor agonists (GLP-1RAs), are attracting increasing attention. This study sought to assess the cost effectiveness for weight loss of 4 GLP-1RAs in adult patients with obesity in the United States.Methods: Four GLP-1RA groups that received Liraglutide (1.8 mg QD), Semaglutide (1.0 mg QW), Dul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
0
18
0
1
Order By: Relevance
“…As a long‐term weight‐control therapy, semaglutide 2.4 mg is estimated to be cost effective compared to untreated D&E alone 40 . Among the four GLP‐1RAs including liraglutide (1.8 mg QD), semaglutide (1.0 mg, once per week), dulaglutide (1.5 mg once per week), or exenatide (10μg, twice per day), semaglutide provided a cost‐effective strategy with an incremental cost‐effectiveness ratio of $135,467/quality‐adjusted life years (QALY) 41 . The use of GLP‐1 agonists to reverse prediabetes with overweight/obesity may be economically feasible and sustainable.…”
Section: Discussionmentioning
confidence: 99%
“…As a long‐term weight‐control therapy, semaglutide 2.4 mg is estimated to be cost effective compared to untreated D&E alone 40 . Among the four GLP‐1RAs including liraglutide (1.8 mg QD), semaglutide (1.0 mg, once per week), dulaglutide (1.5 mg once per week), or exenatide (10μg, twice per day), semaglutide provided a cost‐effective strategy with an incremental cost‐effectiveness ratio of $135,467/quality‐adjusted life years (QALY) 41 . The use of GLP‐1 agonists to reverse prediabetes with overweight/obesity may be economically feasible and sustainable.…”
Section: Discussionmentioning
confidence: 99%
“…3,15 A recent study attempted to calculate quality-adjusted life years indirectly for glucagon-like peptide-1 agonists based on existing data and found that semaglutide was the most costeffective of the drugs tested. 16 Tirzepatide is first in a new drug class that also induces clinically relevant weight reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we did not model the adverse effects of liraglutide since the most common adverse effects of liraglutide 3.0 mg are nausea and diarrhea (as compared to placebo) ( Pi-Sunyer et al, 2015 ) and the evaluation of impacts of the most common adverse effects (i.e., nausea, diarrhea) on QoL is challenging and available data is limited. Therefore, for example, recently published studies have not considered the impacts of adverse effects of liraglutide ( Shah et al, 2018 ; Lee et al, 2020 ; Hu et al, 2022 ). Thus, for simplicity, we did not consider the impacts of adverse effects on QoL or costs.…”
Section: Discussionmentioning
confidence: 99%